ANALISIS PERCEPATAN JADWAL PELAKSANAAN PROYEK DENGAN METODE PERT DAN CPM (STUDI KASUS PEMBANGUNAN VILLA PANBIL TYPE JIMBARAN BLOK R.12) - Harry Kurniawan (Fakultas Teknik, Universitas Riau Kepulauan, 2021)
Planning a good time and cost is needed in the implementation of the project a controling can easily be done to ensure that the implementation of the project has been set can be achieved with minimal deviation and the most satisfactory results by utilizing existing resources. Network Analysis Technique aims to describe and determine the relationships between the various activities and various interpretations of time required for each activity in the project plan as a whole by using the method of CPM and PERT. The project, which became the object of research the author is Construction of Villa Panbil Type Jimbaran Block R.12 at PT. HARAPAN JAYA SENTOSA, in the Villa Panbil area of Batam City, Riau Islands. Based on the research results and calculations using the Network Analysis Technique, it can be concluded that the planning time and costs in particular by using CPM is the most ideal conditions at the time of project performance evaluation with earned value method in a project completion with the result of the optimal time of 258 days where 59 days, faster than the project schedule determined by PT. HARAPAN JAYA SENTOSA which is 317 days at a cost of Rp. 2,483,815,917.-.